2019
DOI: 10.1038/s41398-019-0381-1
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET underscores the key role of the thalamus in frontotemporal lobar degeneration caused by C9ORF72 mutations

Abstract: C9ORF72 mutations are the most common cause of familial frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). MRI studies have investigated structural changes in C9ORF72-associated FTLD (C9FTLD) and provided first insights about a prominent involvement of the thalamus and the cerebellum. Our multicenter, 18F-fluorodeoxyglucose positron-emission tomography study of 22 mutation carriers with FTLD, 22 matched non-carriers with FTLD, and 23 cognitively healthy controls provided valuable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 43 publications
4
20
1
Order By: Relevance
“…Our structural connectivity results were in agreement with the fixel-based results suggesting that both techniques were able to detect WM impairments in FTD. In addition, we found that one of the largest reductions in structural connectivity was between thalamo-frontal regions, supporting the finding that thalamic atrophy is a prominent feature of FTD ( Diehl-Schmid et al, 2019 ) and that it is common across episodic and genetic mutation ( Bocchetta et al, 2018 ).…”
Section: Discussionsupporting
confidence: 83%
“…Our structural connectivity results were in agreement with the fixel-based results suggesting that both techniques were able to detect WM impairments in FTD. In addition, we found that one of the largest reductions in structural connectivity was between thalamo-frontal regions, supporting the finding that thalamic atrophy is a prominent feature of FTD ( Diehl-Schmid et al, 2019 ) and that it is common across episodic and genetic mutation ( Bocchetta et al, 2018 ).…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, one study found that ∼80% of PGRN mutation carrying patients had glucose hypometabolism in the temporal regions of the brain, which extended beyond the boundaries of the frontotemporal region ( Licata et al, 2020 ). C9 carriers were found to have glucose hypometabolism extending into the cerebellar cortex, occipital cortex, cingulate cortex, rolandic operculum, and caudate nuclei ( Castelnovo et al, 2019 ; Diehl-Schmid et al, 2019 ). Furthermore, C9 carriers also showed a characteristic thalami glucose hypometabolism ( Diehl-Schmid et al, 2019 ).…”
Section: Impaired Glucose Metabolism In Frontotemporal Dementia Patientsmentioning
confidence: 99%
“…C9 carriers were found to have glucose hypometabolism extending into the cerebellar cortex, occipital cortex, cingulate cortex, rolandic operculum, and caudate nuclei ( Castelnovo et al, 2019 ; Diehl-Schmid et al, 2019 ). Furthermore, C9 carriers also showed a characteristic thalami glucose hypometabolism ( Diehl-Schmid et al, 2019 ). With over 70 FTD causal MAPT pathogenic mutations known to date, glucose hypometabolic patterns have been harder to establish across MAPT mutation carriers ( Clarke et al, 2021 ).…”
Section: Impaired Glucose Metabolism In Frontotemporal Dementia Patientsmentioning
confidence: 99%
“…The neighboring internal capsule with compact fiber bundle may also be involved, inducing the inhibition of the cortico-ponto-cerebellar pathway. Moreover, striatum and thalamus were also considered to be involved in the process of cognitive function ( Diehl-Schmid et al, 2019 , Hirata et al, 2015 , Leisman and Melillo, 2013 ). These findings may provide a new insight into not only the hemiataxia, but also the cognitive and behavior comorbidities of CCD ( Devita et al, 2021 , Leisman and Melillo, 2013 ).…”
Section: Discussionmentioning
confidence: 99%